2017
DOI: 10.1177/1532673x17715620
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Electoral Impact of the 2010 Oregon Citizens’ Initiative Review

Abstract: The Oregon Citizens’ Initiative Review (CIR) distinguishes itself by linking a small deliberative body to the larger electoral process. Since 2010, CIR citizen panels have been a legislatively authorized part of Oregon general elections to promote a more informed electorate. The CIR gathers a representative cross-section of two dozen voters for 5 days of deliberation on a single ballot measure. The process culminates in the citizen panelists writing a Citizens’ Statement that the secretary of state inserts int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 71 publications
(70 reference statements)
1
50
0
Order By: Relevance
“…In Arizona, 22 participants examined Proposition 205, which proposed ‘legalizing the possession and consumption of marijuana by persons who are 21 years of age or older’ (Gastil, Reedy, et al., ). In Oregon, 20 participants scrutinized Measure 97, which would have removed the cap on the corporate gross sales tax and tax all sales in excess of $25 million at 2.5 percent (Gastil et al, ). In Massachusetts, 20 participants studied the Massachusetts Marijuana Legalization Initiative, which proposed to “legalize marijuana but regulate it in ways similar to alcoholic beverages” (Gastil, Knobloch, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In Arizona, 22 participants examined Proposition 205, which proposed ‘legalizing the possession and consumption of marijuana by persons who are 21 years of age or older’ (Gastil, Reedy, et al., ). In Oregon, 20 participants scrutinized Measure 97, which would have removed the cap on the corporate gross sales tax and tax all sales in excess of $25 million at 2.5 percent (Gastil et al, ). In Massachusetts, 20 participants studied the Massachusetts Marijuana Legalization Initiative, which proposed to “legalize marijuana but regulate it in ways similar to alcoholic beverages” (Gastil, Knobloch, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In general, we should expect that wide publicity is attached to more institutionalised and empowered PIs such as referendums, national-level deliberative citizen assemblies and institutionalised citizens' initiative reviews (Gastil et al 2018). The causal effects on procedural fairness articulated in H1 and H3 necessitate that citizens are at least to some extent aware of how decisions are made in their jurisdictions, and what kinds of participation possibilities there are available.…”
Section: Mode Of Communicationmentioning
confidence: 99%
“…Papadopoulos & Warin 2007b), but empirical research on this topic remains scarce. In general, we should expect that wide publicity is attached to more institutionalised and empowered PIs such as referendums, national-level deliberative citizen assemblies and institutionalised citizens' initiative reviews (Gastil et al 2018). In these types of processes, publicity is exercised by the government, interest groups and media.…”
Section: Mode Of Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…These random samples of citizens exercise various forms of influence. Minipublics, in particular, have formulated referendums on policy controversies (Warren and Pearse 2008), created voting aids on ballot measures to educate fellow voters (Gastil, Knobloch, Reedy, Henkels, et al 2018), and exercised authority over political redistricting (Ancheta 2014). Researchers following these and other deliberative institutions have found that they generally fulfill their promise as a means of promoting better judgment, democratic civic attitudes, and future political engagement (Pincock 2012).…”
mentioning
confidence: 99%